Urinary levels of phthalate metabolites and associations with demographic characteristics in Korean adults - Lee, Kyoung-Mu; Kho, Younglim; Kim, Pan-gyi; Park, Seok-hwan; Lee, Jin-Heon (Environmental science and pollution research international, 2017)
The objective of this study is to assess human exposure to phthalates and its associations with demographic characteristics of the subjects in the Korean National Human Biomonitoring Survey. The subjects aged between 18 and 69 were selected through nationwide stratified sampling. A total of 1874 urine samples were collected and stored at −20 °C until measurement for ten selected metabolites of phthalates (MnBP, MiBP, MBzP, MCHP, MnOP, MEHP, MEOHP, MEHHP, MiNP, and MiDP) using high-performance liquid chromatography-tandem mass spectrometry (LC-MS/MS). The difference in the level of urinary phthalate metabolites by the characteristics of the subjects was tested for statistical significance using SAS Surveyreg procedure. The coefficients and standard errors from multiple linear regressions were exponentiated to estimate the adjusted proportional change (APC) and 95% CIs compared with a referent level. The proportion of data above LOQ was less than 20% for MCHP, MnOP, MiNP, and MiDP. Geometric means of creatinine-adjusted concentrations (unit: μg/g creatinine) of six other phthalate metabolites among Korean adults were 41.7 (95% CI 39.6–43.9) for MnBP, 17.1 (95% CI 16.1–18.1) for MiBP, 15.7 (95% CI 14.4–17.1) for MBzP, 8.65 (95% CI 8.10–9.22) for MEHP, 17.5 (95% CI 16.8–18.3) for MEOHP, and 38.1 (95% CI 36.2–40.2) for MEHHP. Urinary level of phthalates tended to be higher among subjects with older age, females, and those with vigorous daily physical activity and tended to be lower among drinkers and those with higher income. Our results suggest that the level of phthalate exposure is significant among Korean adults and thus warrants further studies to identify major source and route of exposure to phthalates.